2022
DOI: 10.3389/fsurg.2022.843987
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Immuno-Chemotherapy: A New Perspective for Stage III NSCLC?

Abstract: BackgroundStage III Non-small cell lung cancer (NSCLC) is a heterogenous disease with novel treatment options. Recently, immunotherapy has attracted a lot of attention for advanced NSCLC.ObjectiveThe objective of our study was to assess the efficacy and safety of neoadjuvant immuno-chemotherapy for resectable stage III NSCLC.MethodsWe analyzed 11 stage III primary NSCLC surgical cases who had undergone standard lobectomy or bronchial sleeve resection and lymph node dissection between December 2020 and July 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Although there are more limited reports of sleeve resection following neoadjuvant chemo-immunotherapy, a few studies have demonstrated that it is feasible yet technically challenging. One study reported a 30% rate of conversion from VATS to a hybrid approach which may be similar to that described in this study (13), while another group was more successful in using a single port VATS approach with only one of eleven patients requiring thoracotomy (14). Given this evidence, for patients requiring sleeve resections with the potential for additional technical challenges due to neoadjuvant chemoimmunotherapy, it is reasonable to consider evaluating the anatomy first with thoracoscopy before determining whether a VATS, hybrid, or open thoracotomy approach would be safest.…”
supporting
confidence: 81%
“…Although there are more limited reports of sleeve resection following neoadjuvant chemo-immunotherapy, a few studies have demonstrated that it is feasible yet technically challenging. One study reported a 30% rate of conversion from VATS to a hybrid approach which may be similar to that described in this study (13), while another group was more successful in using a single port VATS approach with only one of eleven patients requiring thoracotomy (14). Given this evidence, for patients requiring sleeve resections with the potential for additional technical challenges due to neoadjuvant chemoimmunotherapy, it is reasonable to consider evaluating the anatomy first with thoracoscopy before determining whether a VATS, hybrid, or open thoracotomy approach would be safest.…”
supporting
confidence: 81%
“…TRAEs were graded using the Common Terminology Criteria for Adverse Events (CTCAE), with TRAEs graded ≥3 being considered serious adverse events (SAEs). Eighteen studies have assessed TRAEs ( 5 , 6 , 8 10 , 13 16 , 18 21 , 23 , 28 , 30 , 30 , 34 , 35 , 40 , 43 , 47 , 48 ), and their incidence ranges from 17–100%. The pooled ES was 0.70 (95% CI 0.56–0.81; I²=96.02%) ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled ES was 0.70 (95% CI 0.56–0.81; I²=96.02%) ( Figure 3D ). Twenty-five studies have evaluated SAEs ( 5 , 6 , 8 16 , 18 21 , 25 28 , 30 , 31 , 35 37 , 39 , 40 , 42 , 45 48 ), such as myelosuppression, gastrointestinal reactions, and immune-related target organ or tissue injury. The pooled ES was 0.17 (95% CI 0.10–0.25; I²=93.35%) ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…There was high interrater agreement in terms of study selection (κ = 0.979; p = .021). Table 1 displays pertinent details of each study 13–78 ; patients most commonly had stage III disease and received two to four cycles of various ICIs.…”
Section: Resultsmentioning
confidence: 99%